
#1
Apr2309, 10:26 PM

P: 233

can someone show me how to derive
E_a;b + E_b;a = g_ab E^c; _c I understand the equation E_a;b + E_b;a = 0 but when g_ab dx^a dx^b =0 why can you have E_a;b + E_b;a = g_ab E^c;_c ? 


Register to reply 
Related Discussions  
Conformal group, Conformal algebra and Conformal invariance in field theory  Physics Learning Materials  39  
a naive question about killing vectors  General Physics  3  
Re: a naive question about killing vectors  General Physics  0  
Problem with killing vectors  Special & General Relativity  4 